2019
DOI: 10.1051/matecconf/201927405002
|View full text |Cite
|
Sign up to set email alerts
|

Application of fibre composite grids as reinforcement of foamed PC and GP concrete

Abstract: Cellular concretes cannot be reinforced as easily as traditional ones. Generally porous materials do not ensure sufficient bond of reinforcement; additionally, due to limited amount of aggregate, interlock between aggregate particles and reinforcement ribs is not satisfactory. The idea of reinforcement presented in the paper incorporates bi-directional composite reinforcing grids placed in tensile zone of the cellular concrete slab where transverse fibres are ensuring anchorage for fibres located in the main d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…There were several attempts to investigate foamed geopolymers reinforced by fibers. Most of the research was dedicated to reinforcement by artificial fibers such as carbon [27][28] or glass [29][30], including waste products [29][30]. Some of the investigations have been done on the composites with natural fibers such as hemp [31][32], abaca [33], cellulose [34][35] and jute [36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were several attempts to investigate foamed geopolymers reinforced by fibers. Most of the research was dedicated to reinforcement by artificial fibers such as carbon [27][28] or glass [29][30], including waste products [29][30]. Some of the investigations have been done on the composites with natural fibers such as hemp [31][32], abaca [33], cellulose [34][35] and jute [36].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the investigations have been done on the composites with natural fibers such as hemp [31][32], abaca [33], cellulose [34][35] and jute [36]. The mineral fibers; for example, basalt have been also tested [28,37].…”
Section: Introductionmentioning
confidence: 99%
“…One such material of interest currently being extensively used is basalt fiber, which is cost-effective and offers exceptional properties over glass fibers [73]. Despite the many benefits of using basalt fiber in concrete, only a restricted number of research has been found in the literature concerning basalt fiber or mesh reinforced construction layer of pavements [74][75][76][77]. The authors' long-term research of climatic changes of CE [17][18][19]57,60] and research in the field of applicability of foam concrete with a bulk density of 500 kg•m −3 in transport constructions [48][49][50] created credibility conditions for the design cycle pavements using composite foam concrete (CFC) with basalt mesh at high altitudes of CE.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, it is used as non-structural element of sandwich wall and slab elements, where the light weight and thermal insulation properties of foamed concrete are also used [ 7 ]. At last, foamed concrete can also be combined with steel reinforcement as the main structural element [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%